PREGNANCY - THE STATE OF CHANGES IN THE FIELD OF MOTIVATION ASPECTS FOR SPORT EXERCISING TOO - Anja Fetih Podlesnik (University of Banja Luka, Faculty of physical education and sport, 2010)
The article presents the results of the survey among 163 pregnant women before pregnancy, atthe end of the first triad, and at the end of the second triad of pregnancy. The survey questionsencompass the field of motivation for sport activity. The questionnaire consists of 23 statementsconcerning the motivation before and 25 statements concerning motivation during pregnancy.Individuals define their own motive for sport activity on the five-degree scale. We analyzed therepetition frequencies of all the motives in all three stages of pregnancy and established the crucialmotives for engaging in sport activities before and during pregnancy. Motivational structuresare relatively permanent structures of cognitive-conative area which begin to form in the earlychildhood; therefore we expect these chosen motives to appear in all stages. We ascertained thatpregnant women should be as much as possible acquainted with the influence and significance ofsport activity on their own and their child's health and wellbeing since these are the leading motivesin all three stages of our measuring. Motives within motivational structure may change inspecific circumstances. This is established by our findings as well as during pregnancy the motivesof health of unborn child and positive influence of mother's well being on child take highfrequencies of occurrence.